Globalization and Environmental Challenges Reconceptualizing Security in the 21st Century - Brauch, Hans Günter; Oswald Spring, Úrsula; Mesjasz, Czeslaw; Grin, John; Dunay, Pál; Behera, Navnita Chadha; Chourou, Béchir; Kameri-Mbote, Patricia; Liotta, P. H. (Hexagon Series on Human and Environmental Security and Peace,, 2008)
Globalization and Environmental Challenges pose new security dangers and concerns. In this reference book on global security thinking, 92 authors from five continents and many disciplines, from science and practice, assess the global reconceptualization of security triggered by the end of the Cold War, globalization and manifold impacts of global environmental change in the early 21st century. In 10 parts, 75 chapters address the theoretical, philosophical, ethical and religious and spatial context of security; discuss the relationship between security, peace, development and environment; review the reconceptualization of security in philosophy, international law, economics and political science and for the political, military, economic, social and environmental security dimension and the adaptation of the institutional security concepts of the UN, EU and NATO; analyze the reconceptualization of regional security and alternative security futures and draw conclusions for future research and action. This book contains carefully revised papers from three workshops at ISA (Montreal), IPRA (Sopron) and the Fourth Pan European Conference on International Relations (The Hague) and additional commissioned papers. All chapters were anonymously peer reviewed.